Cost effectiveness of guided Internet‐based interventions for depression in comparison with control conditions: An individual–participant data meta‐analysis. Issue 3 (12th January 2018) - Kolovos, Spyros; van Dongen, Johanna M.; Riper, Heleen; Buntrock, Claudia; Cuijpers, Pim; Ebert, David D.; Geraedts, Anna S.; Kenter, Robin M.; Nobis, Stephanie; Smith, Andrea; Warmerdam, Lisanne; Hayden, Jill A.; et al.
Abstract : Background: There is limited evidence on the cost effectiveness of Internet‐based treatments for depression. The aim was to evaluate the cost effectiveness of guided Internet‐based interventions for depression compared to controls. Methods: Individual–participant data from five randomized controlled trials (RCT), including 1, 426 participants, were combined. Cost‐effectiveness analyses were conducted at 8 weeks, 6 months, and 12 months follow‐up. Results: The guided Internet‐based interventions were more costly than the controls, but not statistically significant (12 months mean difference = €406, 95% CI: − 611 to 1, 444). The mean differences in clinical effects were not statistically significant (12 months mean difference = 1.75, 95% CI: − .09 to 3.60 in Center for Epidemiologic Studies Depression Scale [CES‐D] score, .06, 95% CI: − .02 to .13 in response rate, and .00, 95% CI: − .03 to .03 in quality‐adjusted life‐years [QALYs]). Cost‐effectiveness acceptability curves indicated that high investments are needed to reach an acceptable probability that the intervention is cost effective compared to control for CES‐D and response to treatment (e.g., at 12‐month follow‐up the probability of being cost effective was .95 at a ceiling ratio of 2, 000 €/point of improvement in CES‐D score). For QALYs, the intervention's probability of being cost effective compared to control was low at the commonly accepted willingness‐to‐pay threshold (e.g., at 12‐month follow‐up the probability was .29 and. 31 at a ceiling ratio of 24, 000 and 35, 000 €/QALY, respectively). Conclusions: Based on the present findings, guided Internet‐based interventions for depression are not considered cost effective compared to controls. However, only a minority of RCTs investigating the clinical effectiveness of guided Internet‐based interventions also assessed cost effectiveness and were included in this individual–participant data meta‐analysis.